2003
DOI: 10.1556/abiol.54.2003.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulated acid rain on the pollen germination and pollen tube growth of apple (Malus sylvestrisMiller cv. Golden)

Abstract: The pollens of apple flowers have been treated with simulated acid rain solutions in range of pHs 2.9 to 5.0 in order to determine the threshold proportion values that lead the observed symptoms of detriments of acid rain. Compared to controls (pH 6.5), pollen germination decreased by 41.75% at pH 3.3 and pollen tube elongation decreased by 24.3% at pH 3.4. Acid rain threshold proportion value was around pH 3.3 and 3.4 for apple pollen germination and pollen tube elongation, respectively. Furthermore, pollen t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…The inhibitory effect of metals on cell expansion and division might be due to inhibition of growth promoters primarily through blocking enzyme activation and lowering or direct blocking of cell division by intrusive with the cell membrane integrity [13]. These results of present study agreed with findings on the Cluster Bean [14] wheat [10] the Psyllium and on Mung bean .…”
Section: Figsupporting
confidence: 91%
“…The inhibitory effect of metals on cell expansion and division might be due to inhibition of growth promoters primarily through blocking enzyme activation and lowering or direct blocking of cell division by intrusive with the cell membrane integrity [13]. These results of present study agreed with findings on the Cluster Bean [14] wheat [10] the Psyllium and on Mung bean .…”
Section: Figsupporting
confidence: 91%
“…For example, failure to produce seeds in soybean treated with nZnO (500 mg kg −1 ) was attributed to the significant accumulation of Zn (Yoon et al 2013). According to Munzuroglu and Gur (2000), Zn decreases pollen grain germination and pollen tube growth.…”
Section: Elemental Uptakementioning
confidence: 99%
“…It also decreases the growth of forest trees (Osu and Expo 2013). A number of studies have shown that acid rains have serious effects on vegetative organ and generative structure [3,4]. Acid rain induces changes in cellular biochemistry and whole plant physiology.…”
Section: Introductionmentioning
confidence: 99%